Complement levels and anti-C1q autoantibodies in patients with neuropsychiatric systemic lupus erythematosus. (July 2016) - Magro-Checa, C; Schaarenburg, R A; Beaart, H J L; Huizinga, T W J; Steup-Beekman, G M; Trouw, L A
Objective: The objective of this paper is to analyse serum levels of anti-C1q, C1q circulating immune complexes (CIC), complement activation and complement components in systemic lupus erythematosus (SLE) patients during the first central nervous system neuropsychiatric (NP) event and to define the possible association between these results and clinical and laboratory characteristics. Methods: A total of 280 patients suspected of having NP involvement due to SLE were recruited in the Leiden NPSLE-clinic. All SLE patients were classified according to the ACR 1982 revised criteria for the classification of SLE. The clinical disease activity was measured by the SLE Disease Activity Index 2000 (SLEDAI-2K) and NP diagnoses were classified according to the 1999 ACR case definitions for NPSLE. We measured in serum of all patients anti-C1q and C1q CIC levels, the activation capacity of complement (CH50 and AP50) and different complement components (C1q, C3, C4). Results: In 92 patients the symptoms were attributed to SLE. NPSLE patients consisted of 63 patients with focal NPSLE and 34 patients with diffuse NPSLE. Anti-C1q antibodies were significantly higher and CH50, AP50 and C3 were significantly lower in NPSLE patients compared with SLE patients without NPSLE. This association was specially marked for diffuse NPSLE while no differences were found for focal NPSLE. After using potential predictors, decreased C4 remained significantly associated with focal NPSLE, but only when antiphospholipid antibodies (aPL) were included in the model. C3 and AP50 were independently associated with diffuse NPSLE. When SLEDAI-2K was included in the model these two associations were lost. When individual NPSLE syndromes were analysed, psychosis and cognitive dysfunction showed significantly lower values of complement activation capacity and all complement components. No significant associations were seen for other individual NPSLE syndromes. Conclusion: The associations between diffuse NPSLE and anti-C1q, C3/AP50 and focal NPSLE and C4 may be explained by disease activity and the presence of aPL, respectively. The role of complement activation and complement components in lupus psychosis and cognitive dysfunction merits further research.